A Straightforward Approach to Tetrahydroindolo[3, 2‐b]carbazoles and 1‐Indolyltetrahydrocarbazoles through [3+3] Cyclodimerization of Indole‐Derived Cyclopropanes. Issue 4 (18th December 2015) - Ivanova, Olga A.; Budynina, Ekaterina M.; Khrustalev, Victor N.; Skvortsov, Dmitriy A.; Trushkov, Igor V.; Melnikov, Mikhail Ya.
Abstract: Invited for the cover of this issue is the group of Ekatarina Budynina and co‐workers from M. V. Lomonosov Moscow State University. The image depicts an improvised exhibition wherein an analogy is drawn between dimerization as chemical processes and dimerization as phenomena surrounding us in our everyday life. Read the full text of the article at10.1002/chem.201502287 . Abstract : " Dimerization itself is a very exciting process that fascinates chemists due to the simplicity of its synthetic realization " Read more about the story behind the cover in the Cover Profile and about the research itself on page 1223 ff. (DOI:10.1002/chem.201502287 ).